Aspects of FAIRness for Research Software Registries. - Herbst, W.; Draeger, C.; Perbix, M.; Winter, A.; Lobe, M. (Stud Health Technol Inform, 2025)
Research software registries play an integral role in the process of making software findable, accessible, interoperable and reusable (FAIR). However, there are no guidelines available for FAIRifying registries listing research software. Identifying applicable criteria is a necessary step to develop recommendations that apply to software registries and can later be utilized to measure and improve their FAIRness. Principles that relate to FAIR research software were mapped to granular metrics. Afterwards, registry-applicable aspects were selected and summarized. This resulted in 17 aspects directed at metadata listed in research software registries. Each aspect is expressed in three tables, allowing easy access to relevant information as well as resolvable references to previous works regarding FAIRification. These can be used to develop new, quantifiable metrics. They also provide a meaningful reference point when establishing or improving such registries, an increasingly relevant field in light of the upcoming international initiatives, such as the EOSC.
Keywords: *Registries/standards; *Software/standards; Humans; *Biomedical Research/standards; Metadata